IDENTIFIKASI DAERAH RAWAN ROB UNTUK EVALUASI TATA RUANG PEMUKIMAN DI KABUPATEN DEMAK - Kusuma, Adi Chandra; Irwani, Irwani; Widada, Sugeng (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Banjir rob is when an area inundated during the highest tide and low tide again at the lowest tide. The factor of banjir rob is the height of land, land subsidence, the distance from coastal, and the distance from river. Identification of rob prone areas in Demak is a measure of disaster mitigation to minimize the negative impact of the banjir rob that inundated settlement areas. The purpose of this study is to map the rob prone areas and evaluate the rob prone areas to the spatial planning of settlement area in Demak District. There are five classes of rob prone that inundating settlement area in Demak including the very prone class 14.464 ha, prone class 103.906 ha, the less safe class 335.472 ha, safe class 877.394 ha, very safe class 117 1,527 ha. Areas that included in very prone and prone classes are in Sriwulan Village, Bedono, Timbul loko, Bedono, Surodadi, Tambak bulusan, Morodemak, Purworejo, Betahwalang, Wedung, Berahankulon, and Kedungmutih. Areas that included in less safe, safe, and very safe spread classes are spreading on all villages in Demak District.